A preliminary investigation into diet adequacy in senior residents of Newfoundland and Labrador, Canada: a cross-sectional study - Yan, Jing; Liu, Lin; Roebothan, Barbara; Ryan, Ann; Chen, Zhi; Yi, Yanqing; Wang, Peizhong (BMC public health, 2014)
Adequate dietary intake is essential to maintain good health. This is particularly true for the elderly. This study investigated the dietary intakes of seniors residing in Newfoundland and Labrador (NL) and assessed the adequacy of nutrients which they consumed as food. Between November 2012 and January 2013, we recruited senior residents in NL, aged 65 years or older Participants were required to complete two questionnaires, one food-frequency questionnaire (FFQ) and one general health questionnaire (GHQ). Macro- and micro- nutrients in foods consumed were estimated using the Elizabeth Stewart Hands and Associations (ESHA) nutrient analysis software. The nutrient intakes were compared with appropriate components of the dietary reference intakes (DRIs) adopted by Health Canada to determine adequacy. Various descriptive statistical analyses were performed using SPSS. One hundred-and-eleven participants (69 females and 42 males) completed the surveys and were included in the analysis. A considerable portion of subjects were overweight (41.7%) or obese (25%), and had at least one chronic illness (86.5%). Many seniors studied did not meet the daily recommendations for dietary intakes of nutrients supported by Health Canada, notably vitamin E (84.7%) and vitamin D (68.5%). Our study also suggests that about 40% of participants consumed more dietary energy as fat than is recommended. The present study revealed an inadequate consumption of essential nutrients from foods in a noninstitutionalized senior population of NL.